PETROGENETIC SIGNIFICANCE OF ORTHOPYROXENE-FREE GARNET + CLINOPYROXENE + PLAGIOCLASE ± QUARTZ-BEARING METABASITES WITH RESPECT TO THE AMPHIBOLITE AND GRANULITE FACIES - Pattison D.R.M. (My University, 2003)
Orthopyroxene-free garnet + clinopyroxene + plagioclase ± quartz-bearing mineral assemblages represent the paragenetic link between plagioclase-free eclogite facies metabasites and orthopyroxene-bearing granulite facies metabasites. Although these assemblages are most commonly developed under P-T conditions consistent with high pressure granulite facies, they sometimes occur at lower grade in the amphibolite facies. Thus, these assemblages are characteristic but not definitive of high pressure granulite facies. Compositional factors favouring their development at amphibolite grade include Fe-rich mineral compositions, Ca-rich garnet and plagioclase, and Ti-poor hornblende. The generalized reaction that accounts for the prograde development of garnet + clinopyroxene + plagioclase ± quartz from a hornblende + plagioclase + quartz-bearing (amphibolite) precursor is Hbl + Pl + Qtz=Grt + Cpx + liquid or vapour, depending on whether the reaction occurs above or below the solidus. There are significant discrepancies between experimental and natural constraints on the P-T conditions of orthopyroxene-free garnet + clinopyroxene + plagioclase ± quartz-bearing mineral assemblages and therefore on the P-T position of this reaction. Semi-quantitative thermodynamic modelling of this reaction is hampered by the lack of a melt model and gives results that are only moderately successful in rationalizing the natural and experimental data.
Keywords: AMPHIBOLITE; CLINOPYROXENE; GARNET; HIGH PRESSURE GRANULITE; METABASITE; ORTHOPYROXENE